Mathematics, Resilience and High Ability Students - Filgueira Arias, Cándida; Escribano Ródenas, María del Carmen (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
In the present study, we delve into the different academic factors that influence children with High Capabilities (AACC), with high academic results in the subject of Mathematics, and the Resilience that they develop due to the failure in the ways of relating socially, when considering who must face complex learning challenges in areas such as Mathematics. Research points towards a healthy identification and relationship with themselves and with the environment. Mathematics and AACC students, by managing to overcome social relational barriers and marginalization, can transcend and turn it into training for life (Resilience).